Biological Response of Treatment with Saffron Petal Extract on Cytokine-Induced Oxidative Stress and Inflammation in the Caco-2/Human Leukemia Monocytic Co-Culture Model - Federica De Cecco; Sara Franceschelli; Valeria Panella; Maria Anna Maggi; Silvia Bisti; Arturo Bravo Nuevo; Damiano D’Ardes; Francesco Cipollone; Lorenza Speranza (Antioxidants)
The pathogenesis of Inflammatory Bowel Disease (IBD) involves complex mechanisms, including immune dysregulation, gut microbiota imbalances, oxidative stress, and defects in the gastrointestinal mucosal barrier. Current treatments for IBD often have significant limitations and adverse side effects, prompting a search for alternative therapeutic strategies. Natural products with anti-inflammatory and antioxidant properties have demonstrated potential for IBD management. There is increasing interest in exploring food industry waste as a source of bioactive molecules with healthcare applications. In this study, a co-culture system of Caco-2 cells and PMA-differentiated THP-1 macrophages was used to simulate the human intestinal microenvironment. Inflammation was induced using TNF-α and IFN-γ, followed by treatment with Saffron Petal Extract (SPE). The results demonstrated that SPE significantly attenuated oxidative stress and inflammation by downregulating the expression of pro-inflammatory mediators such as iNOS, COX-2, IL-1β, and IL-6 via modulation of the NF-κB pathway. Given that NF-κB is a key regulator of macrophage-driven inflammation, our findings support further investigation of SPE as a potential complementary therapeutic agent for IBD treatment.